Enhancing Gross Motor Skills of Early Childhood through the Giant Snake and Ladder Game - Sa'diyah, Dessy Aulia Fitriyani; Jazuly, Ahmad; Ashadi, Firman (Teaching, Learning, and Development, 2025)
The purpose of this study is to improve the gross motor skills of early childhood in a local kindergarten in East Java, Indonesia. The participants were ten students from Group A in the 2024/2025 school year, consisting of four boys and six girls, involved in two cycles of classroom action research. Documentation and observation were used to collect data, which were analyzed quantitatively. The findings show that early childhood gross motor skills can be improved through the big snake and ladder game. In the first stage, 60% of children demonstrated development in accordance with the not yet developed criteria; after the first cycle of action, this shifted to 40% of children meeting the developing as expected criteria in the second cycle.